Safety and Efficacy of Spironolactone in Dialysis-Dependent Patients: Meta-Analysis of Randomized Controlled Trials - Liu, Jing; Jia, WanYu; Yu, Chen (Frontiers in Medicine, 2022)
Background: Patients with end-stage renal disease(ESRD) are characterized with high risk of heart failure. Although mineralocorticoid receptor antagonists have beneficial effect on relieving cardiac fibrosis and, thus, reduce the incidence of cardiovascular disease and cardiac death, the therapeutic benefits and adverse effects are still controversial. We conducted a meta-analysis to measure the safety and efficacy of spironolactone in patients undergoing dialysis. Methods: A systematic search for randomized controlled trials(RCTs) was performed in PubMed, Embase, and Cochrane databases. Primary outcomes included changes in all-cause mortality(ACM), serum potassium concentration, incidence of hyperkalemia and gynecomastia(GYN). Secondary outcomes included changes in blood pressure(BP), left ventricular mass index(LVMI) and left ventricular ejection fraction(LVEF). Subgroup analysis and sensitivity analysis were further conducted. Results: Fifteen RCTs with 1258 patients were enrolled in this pooled-analysis. Spironolactone treatment significantly decreased ACM(RR=0.42, P<0.0001), CCV(RR=0.54, P=0.008) and LVMI (MD=-6.28, P=0.002), also increased occurrence of GYN(RR=4.36, P=0.0005). However, LVEF(MD=2.63, P=0.05), systolic BP (MD=-4.61, P=0.14) and diastolic BP (MD=-0.12, P=0.94) did not change between two groups after treatment. Although serum potassium concentration was increased(MD=0.22, P<0.0001) after spironolactone supplement, the risk of hyperkalemia remained unchanged(RR=1.21, P=0.31). Further subgroup analysis found more obvious advantageous as well as disadvantageous effects in Asian subjects than European or American ones. Also, with more than 9 months of treatment duration, patients achieved more favorable influence than shorter duration. Conclusions: These results highlight the therapeutic effects of spironolactone on cardiovascular indexes, including ACM, CCV and LVMI. However, the unignorable increase of GYN incidence and serum potassium level indicate that close monitor in dialysis-dependent patients, especially Asian patients, is essential.